METAPHORS AND SIMILES IN VAN GULIK’S SELF-TRANSLATION OF THE CHINESE MAZE MURDER (Universitas Pamulang, 2022)
A prolific and versatile Dutch writer, translator and orientalist Robert Hans van Gulik (1910-1967), aka é«˜ç½—ä½© Gao Luopei, has composed a series of historical detective novels å¤§å”ç‹„å…¬æ¡ˆ Datang Digong An â€˜Celebrated Cases of Judge Deeâ€™, which concerns an illustrious district magistrate and statesman ç‹„ä»æ° Di Renjie (630-704 AD), who competently investigates murder and corruption in Tang (618-907 AD) China. Upon publishing the debut work The Chinese Maze Murder (1951) in English, van Gulik renders it into a Chinese version entitled ç‹„ä»æ°å¥‡æ¡ˆ Di Renjie Qian, which is the only self-translation by the author-cum-translator. In the Chinese version of The Chinese Maze Murder, the vast majority of metaphors and similes are translated by means of conversion and deletion, so they can be regarded as covert translations in the sense of House (1977, 2014).